Efeitos do estradiol na memória e comportamentos afetivos causados pela privação de hormônios ovarianos - Cristiane Perácio Bastos (2015)
Cognitive and affective disorders occurred during the menopause impact woman’s quality of life and reflect impairments in brain function caused by the estrogens decline. The aim of the present study was to investigate the molecular and functional alterations in the brain of female mice that underwent to hormone deprivation. We also investigated the acute affect of estradiol (E2) in these alterations. Ovariectomy (OVX) surgery was used as a model to induce hormonal depletion in mice. Behavioral analyses demonstrated that 12 weeks of OVX is a critical time-point to observe cognitive and affective impairments. OVX changed the expression of estrogen receptors (ERs) in the hippocampus (HIP) and also modified the c-Fos expression in the amygdala (AMY) after cued fear conditioning. Furthermore, in a genetic mice model for obsessive-compulsive disorder (OCD), the OVX worsened the compulsive- and anxiety-like behaviors, although did not change the memory deficit already founded. On the other hand, the estradiol (E2) administration recovered the impairments observed in OCD female mice model. After 12 weeks of OVX, the administration of E2 and agonists of ERs were effective in decreasing the depressive-like behavior, the HIP-dependent memory deficit. However, E2 was ineffective to rescue the anxiety-like behavior and cued fear memory impairment caused by OVX. Together, our results support the hypothesis that long-term ovarian hormones deprivation is able to promote molecular and functional changes in the brain of female mice, as well as worsen the behavioral alterations observed in the OCD mice model. In addition, we demonstrated that acute E2 administration was able to minimize most of the cognitive and affective impairments evaluated, although its effect was more expressive in HIP-dependent functions. Finally, an important finding of the present study was the suggestion that long-term OVX modify the amygdaloid complex excitability, which may compromise the AMY-dependent memory.